The Theory of Citizenship as A Medium in Promoting Public Policy - Tuasikal, Patma; Saleky, Andre Paulus (Penerbit STKIP PGRI Bangkalan, 2018)
This study was aimed to find a theory about the study of civic education developed as a medium in promoting the public policy. This study used a qualitative approach, with the type of library research to explore liberal, communitarian and republican theories, with data sources consisting of textbooks, journals, and magazines with criteria of relevancy principles relating to research. While the technique of data collection using focused study, with primary source method is Th. Marshall and secondary sources of Peter H. Schuck (2003), Pettit 1997 and Thomas Janoski & Brian Gran (2002). This study showed that the theory of civic education on the concept of communitarian republican was very appropriate in promoting public policy, while liberal theory only leads to political democracy about the freedom to express opinions; however other elements were not appropriate because of it against the values of Pancasila.